NEGOSIASI DAN MANAJEMEN KONFLIK (STUDI KASUS MANAJEMEN KONFLIK PADA MITRA DRIVER GOJEK DENGAN PT. GOJEK INDONESIA - Yulia Herman; Annisya Mega Dwi Handayani; Anggun Dea Ananda; Malvin Agustino; Rezky Dwiham Ginting; Adi Neka Fatyandri (Bajang Institute, 2023)
Labour is part of the company's responsibility for welfare in both social, political, cultural and economic aspects. In the working world, businessmen and workers are always in contact, both directly and indirectly. However, there is not uncommon difference of opinion between the two sides due to differences in intent and background. So, it is not uncommon for conflicts between the two, including at PT. Gojek Indonesia. PT Gojek Indonesia is an Indonesian technology company that serves the transportation sector through motorcycle taxi services. As a large company, PT. Gojek Indonesia has many employees and also has many partners who support this company. However, there are many conditions in the field that need to be improved in the management of PT. Gojek Indonesia. This writing itself is basically aimed at analysing conflict management carried out by PT. Gojek Indonesia in the conflict that occurred with the Gojek Driver Partners. To find data, authors use secondary data through literature studies both through journals, news, and so on as a source of data. In addition, the author found that PT. Gojek Indonesia was able to handle this conflict well which was proven through a solution or middle ground that was carried out as a form of conflict resolution.